Analisis Kualitas Layanan Fiber To The Home Berteknologi Gigabit Passive Optical Network Pada Link STO Sukawati - Ari Pradipta, I Made; Sudiarta, P.K.; Sukadarmika, G. (Jurnal SPEKTRUM, 2019)
Gigabit Passive Optical Network is an optical fiber-based access network technology that is able to provide high data rates and bandwidth. With these advantages, PT. TELKOM applies it to IndiHome services. STO Sukawati has just finished the migration process so that an analysis of service quality is needed to ensure that it is in accordance with ITU-T.G.984 standards. The purpose of this study was to study how the quality of the Sukawati STO IndiHome Link service network. The method used in this study is the method of measurement, calculation and simulation. In the data measurement method taken at PT. Telkom. The calculation method is done mathematically and the simulation method uses the OptiSystem program. The results of measurements, calculations and simulations are compared and then classified according to the standard ITU-T G.984. The parameters that are compared are Power Link Budget, Rise Time Budget, BER, and Q-factor. The measurement results for the furthest customers were obtained by Prx, which was -21.823 dBm, in the simulation and calculation obtained -19,964 dBm and -19,985 dBm. For the Rise Time Budget calculation a total rise time of 0.264 ns is still below the maximum rise time of the NRZ signal bit rate of 0.2917 ns. The results of BER and Q-factor were obtained 1.3x10-17 and 8.45857. The quality of the IndiHome network is categorized as feasible, because it meets the ITU-T G.984 standard.